Neutrophil Extracellular Traps in Digestive Cancers: Warrior or Accomplice - Chen, Yuxin; Han, Lulu; Qiu, Xiaoyan; Wang, Gang; Zheng, Junnian (Frontiers in Oncology, 2021)
Neutrophil extracellular traps (NETs), characterized as a complex of extracellular DNA fibers and granule proteins, are generated specifically by neutrophils which play a critical role in host defense and immune regulation. NETs have initially found be crucial for neutrophil anti-microbial function. Recently, a growing body of evidences suggest that NETs are involved in tumorigenesis and cancer progression. However, the function of NETs in cancer is still contradictory which might be due to the variation of research models and the heterogeneity of cancers. Although most of malignant tumors have similar biological behaviors, obvious differences are indeed existing in different systems. The malignant tumors of the digestive system cause the most incidence and mortality of cancer worldwide. In this review, we would focus on the research progresses of NETs in cancers of digestive system in order to provide insights of their role in digestive cancer progression and future research directions.